Organizational Performance Measurement Based on Competitive Intelligence and Strategic Flexibility in the Food Industry - Shahbandi, Mohammadali; Farrokhshad, Hesam (Journal of Research in Marketing (ISSN: 2292-9355), 2019)
Competitive intelligence requires the appropriate conditions to achieve sustainable competitive advantage and improve organizational performance. Strategic flexibility is one of the effective factors. Since organizational performance can be a factor in recognizing the ascension or decline of organizations in the competition, organizations need to new strategies to have a good performance alongside challenges with the optimal use of opportunities. The purpose of this study is to identify the effect of competitive intelligence on organizational performance with the attention to the role of strategic flexibility mediator.